Screening for anxiety and depression in people with psoriasis: a cross‐sectional study in a tertiary referral setting. (1st April 2017) - Lamb, R.C.; Matcham, F.; Turner, M.A.; Rayner, L.; Simpson, A.; Hotopf, M.; Barker, J.N.W.N.; Jackson, K.; Smith, C.H.
Summary: Background: National Institute for Health and Care Excellence guidance recommends assessment of psychological and social well‐being in people with psoriasis. Objectives: To screen systematically for depression and anxiety in patients with psoriasis in routine clinical practice and to identify at‐risk groups for psychiatric morbidity. Methods: Consecutive patients attending a single, tertiary centre over a 10‐month period were invited to complete the Patient Health Questionnaire Depression Scale (PHQ‐9), Generalized Anxiety Disorder Scale (GAD‐7) and Dermatology Life Quality Index (DLQI) as part of IMPARTS: Integrating Mental and Physical Healthcare: Research, Training and Services. Information on demographics, treatment and clinical disease severity was collated from electronic patient records. Regression models were used to identify at‐risk groups for psychiatric morbidity. Results: Of 607 patients included (56·2% on biologics), 9·9% (95% confidence interval 7·5–12·3%) screened positive for major depressive disorder (MDD) and 13·1% (79/604) (95% confidence interval 10·4–15·8%) for generalized anxiety disorder (GAD; GAD‐7 score > 9). Suicidal ideation was reported in 35% of those with MDD; DLQI was < 10 in 38·3% and 45·6% cases of MDD and GAD, respectively. After adjusting for covariates, the risk of MDD or GAD was significantly higher in women and those with severe clinical disease, psoriatic arthritis and previous depression/anxiety. The risk of GAD was significantly increased with Asian ethnicity and use of topical treatments only. Conclusions: Systematic screening for anxiety and depression identifies clinically important levels of depression and anxiety that may be missed using DLQI data alone. Women and those with severe disease, psoriatic arthritis and/or a prior history of psychiatric morbidity may be at particular risk.